ICT IN EDUCATION AND THE USE OF VIRTUAL LEARNING ENVIRONMENTS - Luís Bender, André; Íris Antunes de Carvalho, Antônia; Porto Veiga, Diego; Carla Beserra da Fonseca, Elizangela; Pereira Albuquerque, Hildelane; Jorge Pereira dos Reis, João; Borges Silva Serejo, Marizete; Lúcia Albuquerque, Valéria; Bezerra de Lira, Vildáquita; Manoel da Fonseca, Carlos (Revista Gênero e Interdisciplinaridade, 2024)
In human societies, the desire to adapt the environment to their needs has resulted in technological inventions that have gradually changed the ways of living, social interaction and the ways of producing work, and more recently, Information and Communication Technologies (ICT). With ICT being used as a form of social and everyday interaction and replacing textbooks, a new way of connecting to knowledge and a new student profile has emerged. At the same time, the context of the digital society itself requires the development of skills that enable the critical and creative use of ICT, which is essential for entering the job market and for everyday life itself. Given the increased use of technologies, the idea has emerged that aligns the use of ICT with an educational environment that prepares students for this new reality. As a result, there has been not only the insertion of digital technologies into pedagogical practice, but also artificial intelligence and virtual learning environments, inserting technologies into an educational context called Education 4.0. In this context, the aim of this article is to investigate the possibilities and advantages of using digital technologies as a teaching resource in terms of developing skills and competencies inherent to creation, the critical and creative use of technologies and, more specifically, the use of virtual learning environments in the context of face-to-face teaching in basic education.